Economic Integration and Sovereign Law at Crossroads: Poland and the EU: Array - Ngwakwe, Collins (Acta Universitatis Danubius. Juridica, 2021)
The dire need for economic wellbeing may lure states into economic integration amidst a somewhat passive agreement. This paper aims to isolate the crossroad between the EU economic integration and sovereign law. The prior conceptual basis is on economic utility and passive agreement. The approach is conceptual and applies discourse analysis using the recent unprecedented Poland’s court ruling, which challenges the EU’s supremacy. The paper uncovers a central point of conflict, which is the desire to retain national legal sovereignty and the quest for higher economic utility. Therefore, the paper highlights an intractable crossroad between target economic wellbeing and regaining the supremacy of national sovereign law. This paper contributes the first utility analysis following the recent Poland’s court objection of EU’s supremacy. It is therefore a good reading for university business schools. The economic and ideological contexts of the paper provide practical insight for economic policy makers on economic integration issues. Further research may pursue the possibility that achieving envisaged higher order economic utility may assuage the desire for national sovereignty pursuit.